Relativistic Fe Kα line and ensemble spins of black holes in narrow-line Seyfert 1 galaxies. Issue Volume 10:Issue S312(2014) (7th March 2016) - Yuan, Weimin; Liu, Zhu; Lu, Youjun; Zhou, Xin-Lin
Abstract: While a broad line of the Fe Kα emission is commonly found in the X-ray spectra of typical Seyfert galaxies, the situation is unclear in the case of Narrow Line Seyfert 1 galaxies (NLS1s)—an extreme subset which are generally thought to harbor less massive black holes with higher accretion rates. We report results of our study of the assemble property of the Fe K line in NLS1s by stacking the X-ray spectra of a large sample of 51 NLS1s observed with XMM-Newton. We find in the stacked X-ray spectra a prominent, broad emission feature over 4–7 keV, which is characteristic of the broad Fe Kα line. Our results suggest that a relativistic broad Fe line may in fact be common in NLS1s. The line profile is used to study the average spin of the black holes in the sample. We find, for the first time, that their black holes are constrained to be likely spinning at averagely low or moderate rates as a population. The implications of the results are discussed in the context of the black hole growth in NLS1 galaxies.